Optimalkan Brand Equity Bank Syariah dengan Social Media Marketing Activities dan Word of Mouth - Aguspriyani, Yani; Darmawansyah, Trisna Taufik (Universitas Galuh, 2025)
This study analyzes the impact of Social Media Marketing Activities (SMMA) on Brand Equity in Islamic banking with Word of Mouth (WOM) as a mediating variable. In the Islamic banking sector, SMMA plays an important role in building consumer image and trust. The study uses a quantitative approach with a survey of respondents who are users of Islamic banking services exposed to social media activities. Data analysis was conducted using linear regression models, path analysis, and Sobel tests to assess the direct and indirect impact of SMMA on Brand Equity through WOM as mediation. The results show that SMMA has a positive and significant impact on WOM, which in turn enhances Brand Equity. However, WOM does not fully mediate the relationship between SMMA and Brand Equity. Simultaneously, SMMA and WOM contribute 67.6% to Brand Equity, with the remaining percentage influenced by other variables not examined. The findings indicate that effective social media marketing strategies, supported by positive WOM, can strengthen the Brand Equity of Islamic banking. This research is expected to provide insights for Islamic banking managers to optimize social media in building consumer loyalty and positive perception.